Analysis of Early Reading Ability in Grade II Elementary School Students - Nadia Fitri Jeni; Eko kuntarto; Silvina Noviyanti (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this research is to describe the analysis of an earlier reading ability at second grade of elementary school students as well as factors that affect students' earlier reading ability. Researchers use a qualitative approach with a case study type of research. The data sources in this study were grade 2 teachers and parents of grade 2 SD Negeri 045 /I Sridadi. The data collection techniques used in this study were observation, interviews, and document studies. The data obtained is then analyzed through the stages consisting of data reduction, data presentation, and verification / drawing conclusions. The results showed that out of 16 second grade students of SD Negeri 045/1 Sridadi, it was found that 6 students, namely JA, AC, MR, AI, DA, and MN experienced problems in the realm of an earlier reading ability such as : (a) not being able to recognize letters, (b) reading syllables, (c) spelling words, (d) stringing words into simple sentences, and (e) reading short texts. Those aspects are the benchmark for students to have an earlier reading ability. Then students' difficulty in reading is caused by several factors, namely: (a) lack of interest in learning, (b) lack of self-confidence, (c) preschool education, and (d) attention from parents.